2014
DOI: 10.1016/j.jhydrol.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale approach to invasion percolation of rock fracture networks

Abstract: A multi-scale scheme for the invasion percolation of rock fracture networks with heterogeneous fracture aperture fields is proposed. Inside fractures, fluid transport is calculated on the finest scale and found to be localized in channels as a consequence of the aperture field. The channel network is characterized and reduced to a vectorized artificial channel network (ACN). Different realizations of ACNs are used to systematically calculate efficient apertures for fluid transport inside differently sized frac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Fracture to matrix flow ratios ( q f / q m ) [ Matthäi and Nick , ] averaged over the domain are 141 in x and 268 in y direction for the well‐connected DetflowC_DWC model and are 9.7 and 14.3 for the less connected DetflowC_DLC . The matrix contribution is less than 1% for the well‐connected representation (DWC), and a similar result could probably be reached with a hydraulic channel network including artificial channels for flow through the matrix between dead‐ending fractures [ Ebrahimi et al ., ]. However, q f / q m in the less‐connected representation (DLC) reach ratios below 10 (>10% matrix contribution) for the eastern portion of the domain, where despite a well‐spaced series of E‐W fractures, no cross connectivity is achieved (Figures c and ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fracture to matrix flow ratios ( q f / q m ) [ Matthäi and Nick , ] averaged over the domain are 141 in x and 268 in y direction for the well‐connected DetflowC_DWC model and are 9.7 and 14.3 for the less connected DetflowC_DLC . The matrix contribution is less than 1% for the well‐connected representation (DWC), and a similar result could probably be reached with a hydraulic channel network including artificial channels for flow through the matrix between dead‐ending fractures [ Ebrahimi et al ., ]. However, q f / q m in the less‐connected representation (DLC) reach ratios below 10 (>10% matrix contribution) for the eastern portion of the domain, where despite a well‐spaced series of E‐W fractures, no cross connectivity is achieved (Figures c and ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect on permeability for differences in connectivity between the DWC and DLC networks does signify the degree to which flow channelizes into the matrix at a disconnected fracture tip and over what distance before reaching an adjacent well‐oriented fracture. Such matrix channels between disconnected fractures [ Ebrahimi et al ., ] strongly reduce the effective permeability particularly in the direction of the disconnected fracture set (i.e., roughly aligning to the x axis). The denoted topological differences between the domains (Figure ) stem from nuanced differences in fracture network development under influence of causative stress field and mechanical properties across the platform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that gas slippage or Knudsen diffusion is critical for investigating gas flow in matrix shale, no matter for correcting laboratory permeability or analyzing field data (Javadpour et al, 2007;Freeman, 2010;Schepers et al, 2009;Wang et al, 2009). However, the study of non-linear flow theory is still in the start stage, which is mostly based on theoretical researches (Dreuzy et al, 2012;Wang et al, 2013;Ebrahimi et al, 2014). The most important theory in the early age is the Klinkenberg model (Klinkenberg, 1941).…”
Section: Introductionmentioning
confidence: 99%